The impact of care-recipient relationship type on mental health burden of caregivers for schizophrenia patients: evidence from Beijing, China - Zhu, Yi; Yin, Margaret Xi Can (Frontiers in Psychology, 2024)
Objective: To examine the impact of care-recipient relationship type on mental health burden of caregivers for schizophrenia patients in China, elucidating the underlying mechanisms.A cross-sectional study was conducted using face-to-face surveys administered to caregivers of patients with schizophrenia in selected communities in Beijing, China. 1,853 samples' data was used. Descriptive statistics, logistic regression models and Sheaf coefficient method were employed to analyze the data.The mental health burden experienced by caregivers of schizophrenia patients has reached a high level, with 66.9% reporting a moderate or severe impact from their caregiving responsibilities. Parents and spouses were the primary providers of care for schizophrenia patients in China. Parent caregivers experienced greater suffering in their caregiving role compared to spouse caregivers, whereas the difference between child caregivers and spouse caregivers was not significant. The factors influencing caregiver's mental health burden vary according to the type of relationship with the care-recipient. For parent caregivers, the mental health burden primarily stems from personal conditions of schizophrenia patients, while for spouse or child caregivers, it mainly arises from family economic conditions.This study reveals that caregivers having different types of care-recipient relationship with schizophrenia patients experience significantly different mental health burdens in Beijing, China, and major influencing factors are distinct according to different care-recipient relationship types.